Efficacy and safety of pharmacotherapies for smoking cessation in anxiety disorders: Subgroup analysis of the randomized, active‐ and placebo‐controlled EAGLES trial - Ayers, Catherine R. (Depress Anxiety, 2019)
BACKGROUND: Smoking rates are high in adults with anxiety disorders (ADs), yet little is known about the safety and efficacy of smoking‐cessation pharmacotherapies in this group. METHODS: Post hoc analyses in 712 smokers with AD (posttraumatic stress disorder [PTSD], n = 192; generalized anxiety disorder [GAD], n = 243; panic disorder [PD], n = 277) and in a nonpsychiatric cohort (NPC; n = 4,028). Participants were randomly assigned to varenicline, bupropion, nicotine‐replacement therapy (NRT), or placebo plus weekly smoking‐cessation counseling for 12 weeks, with 12 weeks follow‐up. General linear models were used to test the effects of treatment group, cohort, and their interaction on neuropsychiatric adverse events (NPSAEs), and continuous abstinence weeks 9–12 (treatment) and 9–24 (follow‐up). RESULTS: NPSAE incidence for PTSD (6.9%), GAD (5.4%), and PD (6.2%) was higher versus NPC (2.1%), regardless of treatment. Across all treatments, smokers with PTSD (odds ratio [OR] = 0.58), GAD (OR = 0.72), and PD (OR = 0.53) had lower continuous abstinence rates weeks 9–12 (CAR9–12) versus NPC. Varenicline demonstrated superior efficacy to placebo in smokers with GAD and PD, respectively (OR = 4.53; 95% confidence interval [CI] = 1.20–17.10; and OR = 8.49; 95% CI = 1.57–45.78); NRT was superior to placebo in smokers with PD (OR = 7.42; 95% CI = 1.37–40.35). While there was no statistically significant effect of any treatment on CAR9–12 for smokers with PTSD, varenicline improved 7‐day point prevalence abstinence at end of treatment in this subcohort. CONCLUSION: Individuals with ADs were more likely than those without psychiatric illness to experience moderate to severe NPSAEs during smoking‐cessation attempts, regardless of treatment. While the study was not powered to evaluate abstinence outcomes with these subgroups of smokers with ADs, varenicline provided significant benefit for cessation in those with GAD and PD, while NRT provided significant benefit for those with PD.